Filial Piety: Studi Pengaruh Komitmen Religious, Gratitude, dan Demografi Terhadap Filial Piety - Johara, Rika Rostika; Lutfi, Ikhwan (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
This study aims to determine the effect of the religious commitment, and gratitude on the youth filial piety in Indonesia, particularly in the Ciputat village. The author also adds demographic variables of age and sex to determine their effects on youth filial piety. The sample in this study were 239 youths in the village of Ciputat. The sampling technique used in this research is nonprobability sampling and analysis of the data in this study using multiple regression test. The results indicate that the gratitude and religious commitment affects filial piety. Independent variables are tested using multiple regression, there are five significant independent variable (religious values, religious belief, appreciation for other, age, and gender). These results indicate the proportion of the variance of youth filial piety which explained all the independent variables is 39.2% and 60.8% were influenced by other variables outside the research.Â DOI: 10.15408/tazkiya.v20i2.9167